Ответы 2
Відповідь:
-6,3(3x+6,8y)+1,4(-2x+5y)-(-5,6x+6,8y)=-18,9x+42,84y-2,8x+7y+5,6x-6,8y=-10,5x+43,04y, якщо x=-4, y=-5, то -10,5*(-4)+43,04*(-5)=42-215,2=-173,2
Покрокове пояснення:
Ответ:
-12,2
Пошаговое объяснение:
-6,3(3х - 2,4у) + 1,4(-2х + 5у) - (-5,6х + 6,8у) =
-18,9х + 15,12у - 2,8х + 7у + 5,6х - 6,8у =
(-18,9х - 2,8х + 5,6х) + (15,12у + 7у - 6,8у) =
-16,1х + 15,32у
х = -4; у = -5
-16,1х + 15,32у = -16,1 * (-4) + 15,32 * (-5) =
64,4 + (-76,6) = 64,4 - 76,6 = -12,2
Премиум статус
Получайте самые быстрые
ответы на свои вопросы
ответы на свои вопросы
У вас остались
вопросы?
вопросы?